Comparison of the dielectric and NMR results for liquid crystals: dynamic aspects1. (7th July 2014) - Urban, Stanislaw; Geppi, Marco; Dong, Ronald Y.
<x xml:space="preserve">Abstract</x> Critical analysis of the results of studies of molecular rotational dynamics in liquid crystalline substances with the aid of the dielectric spectroscopy (DS) and nuclear magnetic resonance (NMR) is given. Both methods are known to be sensitive to different aspects of molecular rotations: the polarization vector and the relaxation time τDS in the case of DS, a tensor describing a nuclear interaction and the correlation time τNMR for NMR method. Furthermore, both methods provide correlation functions with different rank values. A common basis for the comparison between τDS and τNMR is postulated. Several examples of the temperature dependence of the correlation times coming from the two spectroscopic methods are presented. Qualitative agreements of the correlation times were achieved in most cases. Copyright © 2014 John Wiley & Sons, Ltd.